Parametric optimization of plastic injection moulding for FMCG polymer moulding (PMMA) using hybrid Taguchi-WASPAS-Ant Lion optimization algorithm. (2022) - Ravikiran, Bammidi; Pradhan, Deepak Kumar; Jeet, Siddharth; Bagal, Dilip Kumar; Barua, Abhishek; Nayak, Sasmita
Abstract: In this fast growing world, the demand for fast-moving consumer goods (FMCG) and half of the goods are manufactured through the use of plastic. To cater to those, plastic goods are manufactured using different types of moulding process. Plastic injection moulding (PIM) is a technique of injecting molten plastic into a mould to form it. They are widely used to manufacture FMCG products like containers, remote cases, or other small, complex profiles. But sometimes these complex profile mouldings lack dimensional accuracy. The current study provides an understanding of the clear thermoplastic Polymethyl Methacrylate (PMMA) material moulding for FMCG items utilizing an injection moulding machine. The transparent top sheath used in male/female deodorants can be considered in this investigation. For the purpose of minimizing weld-line width and sink-marks depth during injection moulding of commercial grade transparent thermo-plastic (Polymethyl Methacrylate), eight plastic injection moulding criteria were considered, namely melting temperature, mould temperature, cooling time, injection pressure, back pressure, holding pressure, ambient temperature, and holding time. In accordance with Taguchi's Design, the 27 experiments were piloted, and the factors were optimized using the Taguchi-based WASPAS method (Weighted Aggregated Sum Product Assessment), the Ant Lion optimization algorithm, and analysis of variance to determine the most dominant parameter in the minimization of weld-line width and sink-mark depth of the plastic injection moulded part. It was discovered that the cooling time of the plastic injection moulded component is the most important element affecting the weld-line width as well as the depth of the sink-mark on the surface of the part.